2016
DOI: 10.5045/br.2016.51.3.171
|View full text |Cite
|
Sign up to set email alerts
|

Establishing the heparin therapeutic range using aPTT and anti-Xa measurements for monitoring unfractionated heparin therapy

Abstract: BackgroundUnfractionated heparin (UFH) has unstable pharmacokinetics and requires close monitoring. The activated partial thromboplastin time (aPTT) test has been used to monitor UFH therapy for decades in Korea, but its results can be affected by numerous variables. We established an aPTT heparin therapeutic range (HTR) corresponding to therapeutic anti-Xa levels for continuous intravenous UFH administration, and used appropriate monitoring to determine if an adequate dose of UFH was applied.MethodsA total of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 11 publications
1
45
0
Order By: Relevance
“…The APTT is a clotting time assay that is useful for diagnosing deficiencies in the coagulation factors of the intrinsic pathway, such as hemophilia, 6 the presence of inhibitors, such as lupus anticoagulant (LA), 7 and acquired hemophilia and for monitoring heparin treatment. 8 All coagulation tests were in the beginning performed by hand and so the timing was done using a stop watch; thus multiple assays and standardization of APTT were difficult to carry out with this manual method. The development of automatic optical coagulation analyzers has made it easy to perform multiple assays and enabled the standardization of the APTT reagents for LA and heparin.…”
Section: The History Of Cwa/apttmentioning
confidence: 99%
“…The APTT is a clotting time assay that is useful for diagnosing deficiencies in the coagulation factors of the intrinsic pathway, such as hemophilia, 6 the presence of inhibitors, such as lupus anticoagulant (LA), 7 and acquired hemophilia and for monitoring heparin treatment. 8 All coagulation tests were in the beginning performed by hand and so the timing was done using a stop watch; thus multiple assays and standardization of APTT were difficult to carry out with this manual method. The development of automatic optical coagulation analyzers has made it easy to perform multiple assays and enabled the standardization of the APTT reagents for LA and heparin.…”
Section: The History Of Cwa/apttmentioning
confidence: 99%
“…The activated partial thromboplastin time (APTT) is an end-point clotting time assay that is useful for diagnosing deficiencies in the intrinsic pathway, such as hemophilia, 1 for diagnosing the presence of lupus anticoagulant (LA), 2 and for monitoring heparin treatment. 3 Automatic optical end-point coagulation analyzers have been recently developed, making it easy to perform multiple assays. Another benefit of optical end-point coagulation analyzers is the ability to visualize the clot reaction curve as the prothrombin time and the APTT.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, in a patient on extracorporeal membrane oxygenation, the APTT may be prolonged into the therapeutic range due to factor deficiencies, and result in decreased heparin dosing that may lead to thrombosis [8]. e APTT is also affected by acute phase reactants and the lupus anticoagulant, and may be affected by liver disease [9]. In fact, it has been suggested that Anti-Xa assay supplant the APTT in patients on heparin therapy, as it may offer a smoother dose-response curve, with fewer blood draws, and fewer dosage adjustments [10].…”
Section: Discussionmentioning
confidence: 99%